2015
DOI: 10.1037/fam0000053
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of family therapy in juvenile drug court.

Abstract: The objective of this article is to examine the effectiveness of 2 theoretically different treatments delivered in juvenile drug court—family therapy represented by multidimensional family therapy (MDFT) and group-based treatment represented by adolescent group therapy (AGT)—on offending and substance use. Intent-to-treat sample included 112 youth enrolled in juvenile drug court (primarily male [88%], and Hispanic [59%] or African American [35%]), average age 16.1 years, randomly assigned to either family ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 59 publications
1
48
1
1
Order By: Relevance
“…Results from individual RCTs have indicated that receiving MDFT decreased drug use involvement and increased prosocial behaviors more than comparison treatments (Liddle et al, 2001, 2008, 2009, 2011; Rigter et al, 2012). MDFT also has been associated with greater decreased delinquent behavior (Dakof et al, 2015; Liddle et al, 2009, 2011)), externalizing behaviors (Liddle et al, 2001), and internalizing symptoms (Liddle et al, 2009). In the five studies included in the current IDA, individual study results indicated that MDFT decreased drug use dependence symptoms to a greater extent than individual cognitive behavioral therapy (Liddle et al, 2008) and adolescent group therapy (Liddle et al, 2009) among community adolescents referred for drug abuse treatment and adolescents enrolled in a post-adjudication juvenile drug court (Dakof et al, 2015).…”
Section: Multidimensional Family Therapy For Adolescent Drug Usementioning
confidence: 99%
“…Results from individual RCTs have indicated that receiving MDFT decreased drug use involvement and increased prosocial behaviors more than comparison treatments (Liddle et al, 2001, 2008, 2009, 2011; Rigter et al, 2012). MDFT also has been associated with greater decreased delinquent behavior (Dakof et al, 2015; Liddle et al, 2009, 2011)), externalizing behaviors (Liddle et al, 2001), and internalizing symptoms (Liddle et al, 2009). In the five studies included in the current IDA, individual study results indicated that MDFT decreased drug use dependence symptoms to a greater extent than individual cognitive behavioral therapy (Liddle et al, 2008) and adolescent group therapy (Liddle et al, 2009) among community adolescents referred for drug abuse treatment and adolescents enrolled in a post-adjudication juvenile drug court (Dakof et al, 2015).…”
Section: Multidimensional Family Therapy For Adolescent Drug Usementioning
confidence: 99%
“…This is a promising finding suggesting that CBT and MDFT might be two effective treatments that can be used to reduce cannabis use among African American youth. Other studies have especially supported the use of family based interventions, such as MDFT, in the treatment of substance use, especially among African American youth in the context of the criminal justice system (Dakof et al, 2015; Henderson, Dakof, Greenbaum, & Liddle, 2010). Given that African American youth are more likely than other racial/ethnic groups to enter the health care system through the legal system (Heflinger, Chatman, & Saunders, 2006; Sinha, Easton, & Kemp, 2003), it is important to identify effective treatments that are tailored for juvenile justice contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the vast documentation on the direct effect of drug abuse on recidivism [23][24][25] there has been paucity of empirical data on its indirect effect. However, a couple of previous studies that consistently highlight the harmonic link between drug abuse, psychopathic personality and recidivism are mentioned [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the paucity of substantial evidence to support drug abuse and illicit psychopathic personality to cause to recidivism studies suggest that substance abuse appeared to provide a pathway between psychosocial characteristics and delinquent decision making [26]. Notably, a study conducted by Hare and Neumann [27] reported that psychopathic personality frequently correlate with substance abuse and other mental and behavioural health problems.…”
Section: Drug Abusementioning
confidence: 99%